«Smart polemos»: artificial intelligence in information wars - Fedorchenko, Sergey N. (Journal of the Belarusian State University. Philosophy and Psychology, 2025)
The article reveals the specific features of using artificial intelligence technologies in modern information wars and conceptualises the political phenomenon of «smart polemos». Within the framework of the new concept of «smart polemos», it is proposed to focus the attention of researchers on the practices of using algorithms in information confrontation, including armed conflicts. A wide range of «smart polemos» technologies is shown (from digital manipulations, digital propaganda, creating deepfakes to combat operations support systems and cyberweapons use practices). It is concluded that, despite the challenges and risks of developing «smart polemos» in the field of supporting information and combat operations, intelligent systems are more often used in digital psychological manipulations. Cases of political intrigue created through the use of artificial intelligence in information operations are studied; the use of a multi-move strategic scenario, the presence of a customer, his goals and a «target»-victim in the structure of these intrigues are noted. In response to the challenges, threats and risks of «smart polemos», an ecumenical approach is proposed which implies the formation of a digital ecumene of the state and its allies.